To Whom Does the Knowledge Belong? The Researcher-Researched Relationship and Vulnerability in Refugee Studies - Krawczyk, Mateusz M.; Kikalage Dieudonné, Joël (ETHICS IN PROGRESS, 2023)
Research ethics address concerns related to power imbalances. These dynamics are particularly prominent in refugee camps, where the contemporary ‘protracted’ state (UNHCR, 2004) turns them into quasi-laboratories, where refugees are subjected to scrutiny, measurement, observation, and analysis by researchers, NGOs, and governmental organizations. Researchers typically conduct brief field trips to perform predetermined scientific activities, limiting their comprehensive understanding of the subject under study. Fieldwork conducted in Nakivale Refugee Settlement (Uganda) since 2019 has highlighted an often-one-way communication dynamic between researchers and refugees, where refugees rarely receive feedback on the information they provide. Consequently, refugees develop a lack of trust towards researchers, impacting their subjectivity and self-esteem. They perceive themselves as information providers rather than owners, lacking simultaneous access to that information. The concept of power-knowledge (Foucault 1980) is instrumental in understanding this issue and reflecting on researchers’ responsibilities in studying vulnerable populations.